Pengaruh Tekstur Dan Struktur Tanah Terhadap Distribusi Air Dan Udara Di Profil Tanah - Zega, Novita Debora (CV. SINAR HOWUHOWU, 2024)
This research aims to explore the influence of soil texture and structure on the distribution of water and air in soil profiles. Using a quantitative approach and a field experiment design, data were were collected from several sites with a variety of soil types, including sandy, dusty and loamy soils. The results showed that loamy soils have higher water retention capacity (35%) and greater total porosity (50%) compared to sandy soils, which only had a 10% water retention capacity and 35% total porosity. In addition, good soil structure, especially in dusty soils, supports optimal air circulation. optimal air circulation. These findings emphasize the importance of proper management soil texture and structure to improve water use efficiency and support sustainable crop growth. and support sustainable crop growth.